Retrospective Radiographic Analysis of Peri-Implant Bone Loss in Mandibular Full-Arch Implant Rehabilitations - Francesco Giordano; Alfonso Acerra; Roberta Gasparro; Marzio Galdi; Francesco D’Ambrosio; Mario Caggiano (Diagnostics, 2024)
Objectives: Can the type of implant rehabilitation influence peri-implant bone loss in case of full-arch mandibular prosthesis? The purpose of the study was to assess, using orthopantomograms (OPGs), the bone loss around implants in different types of implant-supported prosthetic rehabilitations and identify potential risk factors, associated with the number and location of implants, that may have an association with bone defects. Methods: A radiographic study was conducted on 22,317 OPGs from 2010 to 2024. All OPGs with implant-supported prosthetic mandibular rehabilitations were included in the study. Results: A total of 155 OPGs were evaluated, with peri-implant bone loss identified in 64 (41.3%). Distal implants (furthest from the center) across various positioning patterns were most susceptible to bone loss, with positions 3.6 and 4.6 demonstrating the most frequent occurrence (25 and 26 cases, respectively). The χ2 test revealed significant associations between both the implant positioning pattern (p < 0.001) and number of implants (p < 0.001) with peri-implant bone loss. Also, by updating the sample of OPGs, increased susceptibility to bone resorption was found for implants placed distal to the mental foramen compared to mesial ones in full-arch-implant-supported fixed prostheses. Conclusions: Prospective clinical studies will therefore be useful in investigating this finding further.